Discrimination between activators and nonactivators of the alternative pathway of complement: regulation via a sialic acid/polyanion binding site on factor H. - Meri, S (1990)
The alternative complement pathway is capable of discriminating human cells and tissues from a wide variety of potential pathogens. It has been recently demonstrated that attachment of complement component C3b to activator-derived molecules (e.g., small polysaccharides) restricts inactivation of C3b by factors H and I in a manner similar to activator surfaces. It is now shown that restriction is reversed by certain soluble polyanions (e.g., sialoglycopeptides, heparin, or dextran sulfate) that mimic the effects of sialic acid and glycosaminoglycans on human cells and tissues. Fluid-phase polyanions enhanced binding of factor H to C3b attached to activating particles, indicating that the effect resulted from increased affinity between C3b and factor H. The enhancement was specific for activator-bound C3b since no enhancement was observed on nonactivating particles. While several polyanions could cause this effect, some polyanions could not, indicating specificity. The active polyanions also inhibited lysis of cells via the alternative pathway. The binding site for sialic acid appears to reside on factor H, since factor H bound to heparin-agarose and to sialic acid-bearing fetuinagarose, whereas C3b bound to neither under the same conditions. These observations suggest that occupation of a specific site on factor H by polyanions induces an increase in the C3b-H affinity, resulting in discrimination of host cells and tissues from alternative pathway-activating foreign cells.